"Somebody Up There Likes You": Free Will and Determinism on a Journey through Space in Kurt Vonnegut's The Sirens of Titan (1959). (28th September 2017) - Radford, Raymond
Abstract : Kurt Vonnegut's Sirens of Titan (1959) is the story of the world's richest man caught up in the machinations of an unfeeling universe. Vonnegut discusses the place of humanity in the universe, and the problems inherent in society. This novel is used primarily to explore the way that pilgrimage functions in a real, and tangible world, primarily the way that pilgrimage is seen as freedom of choice for when and where a pilgrim will go on pilgrimage. Using Sirens of Titan this article will investigate the concept of free will, choice and determinism within both a fictional world and a real world in which all characters believe they are in control of their own destiny.  Through characters such as Malachi Constant, determinism, religion, free will, and choice shall be explored through the lens of pilgrimage with the expressed desire to find one's self or answers they seek. Free will and determinism is explored through the usage of Sam Harris and Daniel C. Dennett whose theories about free will allow for concepts to be explored within science-fiction and that of real-life pilgrimage, and the change that these journeys bring for the pilgrim. This article shall also explore the context of the journey, be it a quest or a pilgrimage, both of which are performed for higher reasons. These higher reasons are explored as reasons why pilgrimages and quests are undertaken, and whether these journeys are undertaken freely, or has the universe indeed mandated that this is the time and place a pilgrim will undertake their journey.